2017
DOI: 10.3390/su9020232
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Unprocessed Waste Chicken Eggshells for UV-Protective Applications

Abstract: Photodegradation causes a steady loss of the useful physical, mechanical and optical properties of materials, necessitating their replacement over time. Because UV (Ultraviolet) light is most harmful in this regard, many materials now contain UV-protective additives. However, these additives are not always effective and durable, can be expensive, and their natural extraction or synthetic production can be harmful to the environment. Here, we investigated the use of unprocessed chicken eggshells in providing UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
1
Order By: Relevance
“…Fecheyr-Lippens et al [89] explored WCES for the protection of two regularly used synthetic polymers (polystyrene and nylon) from ultraviolet (UV) degradation and reported that unprocessed WCES contains UV-protective additives for the protection of photodegradable materials. The outcome of the investigation further revealed WCES as a novel, cost-effective, durable, and ecologically benign protector of synthetic polymers from UV light and performed better than titanium dioxide (TiO 2 ) and other inorganic additives.…”
Section: Tga Xrd Semmentioning
confidence: 99%
“…Fecheyr-Lippens et al [89] explored WCES for the protection of two regularly used synthetic polymers (polystyrene and nylon) from ultraviolet (UV) degradation and reported that unprocessed WCES contains UV-protective additives for the protection of photodegradable materials. The outcome of the investigation further revealed WCES as a novel, cost-effective, durable, and ecologically benign protector of synthetic polymers from UV light and performed better than titanium dioxide (TiO 2 ) and other inorganic additives.…”
Section: Tga Xrd Semmentioning
confidence: 99%
“…60 Most eggshell waste is discarded without further processing by sending it to landll at a cost of more than $40 a ton depending on the location of the landll. 44,[61][62][63] In recent years, the syntheses of HA from natural sources has been extensively studied by researchers. 64 The abundance of eggshells, the necessity of recycling them to avoid pollution, and the consideration of their elements-and oxides-rich nature have prompted the researchers to study eggshells and investigate the possibility of employing eggshells in important areas as a natural resource.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermost eggshell remaining is thrown away since additional treating is too costly and burdensome 4 . Numerous researchers have been observed for methods to use the eggshells discarded, such as, via eggshells powder as a steadying material for cultivating soil properties, Ultraviolet-protecting essences 5,6 and as a basis of Calcium in human diet 7 .…”
Section: Introductionmentioning
confidence: 99%